An Exploratory Sequential Mixed Method Evaluation Of General Practitioners, Pharmacists, Consumers And Pharmacy Students’ Knowledge, Perception And Attitude On Contemporary Issues Surrounding Generic Medicine Use In Karachi, Pakistan - Jamshed, Shazia (2011)

(untitled)
Developing countries are struggling with the high cost of treatment and Pakistan is not an exception to this issue. Generic medicines could be instrumental in curtailing the cost of treatment and reduce healthcare expenditures in Pakistan. Therefore, it is imperative to ascertain the knowledge, perception and attitudes of different stakeholders in this regard. The study used a sequential mixed-method research in which the qualitative and quantitative approaches were applied. The qualitative data was collected through in-depth semi-structured, face-to-face interviews with general practitioners, pharmacists, consumers, and pharmacy students. Saturation point, a peak after which no new information was sought from additional interviews, was achieved at 11 for doctors, 11 for pharmacists, 29 for consumers and 28 for pharmacy students.